Prevalence of Performance-Enhancing Substances in gym goers in north Cyprus using mixed-methods - Hocaoglu, M.; Cevikel, A.; Mahsereci, I; Aroglan, E.; Dinc, E.; Memisoglu, N.; Cakmak, D. (Oxford Univ Press, 2018)
[Abstract Not Available]